THE EFFECT OF CHANGES IN ACCOUNTING PROFIT AND CASH FLOW COMPONENTS ON STOCK RETURNS INPLANTATION SUBSECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE 2017-2020 - Siti Hajar; Kasmawati Kasmawati; Irfan Tanjung (STIE Bangkinang Publishing, 2022)
This study aims to determine the effect of changes in accounting earnings, operating cash flows, investment cash flows, funding cash flows on stock returns. The sample in this study were 10 plantation sub-sector companies listed on the Indonesia Stock Exchange in 2017-2020. The sampling technique used is purposive sampling. The analysis technique used in this research is multiple linear regression. Based on the results of the simultaneous test of accounting profit variables, operating cash flows, investment cash flows, funding cash flows have a significant effect on stock returns. While partially there are three variables that have a significant effect on stock returns, namely accounting profit, operating cash flow, funding cash flow, while the investment cash flow variable has no significant effect on stock returns. The close relationship that occurs between the variables of accounting profit, operating cash flow, investment cash flow, funding cash flow to stock returns is moderate, with Adj R square of 0.181 or 18.1% while the remaining 81.9% is explained by other variables that are not included. in this research.